1999
DOI: 10.1006/jpho.1999.0095
|View full text |Cite
|
Sign up to set email alerts
|

Perception of suprasegmental structure in a non-native dialect

Abstract: Two experiments examined the processing of Tokyo Japanese pitchaccent distinctions by native speakers of Japanese from two accentlessvariety areas. In both experiments, listeners were presented with Tokyo Japanese speech materials used in an earlier study with Tokyo Japanese listeners, who clearly exploited the pitch-accent information in spokenword recognition. In the "rst experiment, listeners judged from which of two words, di!ering in accentual structure, isolated syllables had been extracted. Both new gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…In all cases, as shown by the F 1 significance, the empirical results were highly consistent across participants, though they were drawn from different parts of Japan (Appendix C). Likewise, Otake and Cutler (1999) found that people from no-accent regions responded to Tokyo dialect stimuli in the same, albeit somewhat attenuated, way as native Tokyo dialect speakers in various recognition experiments. This generalized effect presumably reflects daily exposure from broadcasting (Otake & Cutler, 1999) and also active migration of people.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In all cases, as shown by the F 1 significance, the empirical results were highly consistent across participants, though they were drawn from different parts of Japan (Appendix C). Likewise, Otake and Cutler (1999) found that people from no-accent regions responded to Tokyo dialect stimuli in the same, albeit somewhat attenuated, way as native Tokyo dialect speakers in various recognition experiments. This generalized effect presumably reflects daily exposure from broadcasting (Otake & Cutler, 1999) and also active migration of people.…”
Section: Discussionmentioning
confidence: 80%
“…Likewise, Otake and Cutler (1999) found that people from no-accent regions responded to Tokyo dialect stimuli in the same, albeit somewhat attenuated, way as native Tokyo dialect speakers in various recognition experiments. This generalized effect presumably reflects daily exposure from broadcasting (Otake & Cutler, 1999) and also active migration of people. Moreover, Ueno and colleagues (Ueno, 2012;Ueno et al, 2014) reported the consistent use of accent patterns presented with a Tokyo dialect by their participants drawn from various areas in Japan.…”
Section: Discussionmentioning
confidence: 80%
“…Speech processing by listeners with a different dialect of the same language has received somewhat less research attention, but recent studies have documented challenges presented by this less radical mismatch also. Sumner and Samuel (2009), for instance, found that speakers of a General American dialect can have problems in recognizing words produced with a New York accent, Floccia et al (2006) likewise found an initial processing cost for a different dialect in word recognition tasks, and Otake and Cutler (1999) found that cross-dialect perception of Japanese words exhibited lower sensitivity to information in the signal (d 0 ) and a higher degree of bias (b) toward lexical knowledge. Cross-dialect difficulties in phoneme perception, however, seem to be of lesser magnitude than cross-language difficulties.…”
Section: Introductionmentioning
confidence: 90%
“…Japanese, on the other hand, differs from English mainly because variations in pitch are not accompanied by segmental changes. For speakers of a pitch-accent variety of Japanese, F 0 differences clearly constrain lexical access (Otake and Cutler 1999), indicating that listeners are able to use this F 0 information at the lexical level during on-line spoken word recognition.…”
mentioning
confidence: 99%